2023
DOI: 10.4314/njt.v42i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the physico-chemical quality of Uturu section of Aku river in southeastern Nigeria

O. Chinyere,
Y. Sanusi,
F. Anafi

Abstract: The physicochemical monitoring of water quality is very key both to aquatic life and public health. To date little is known about the water quality downstream of Aku river, located in Uturu, Isuikwato local government area of Abia state. Therefore the aim of the study is to determine the water quality downstream of Aku river in terms of several physicochemical parameters and heavy metals analysis to ascertain the water quality properties and reveal pollution problems. Samples were collected at 15m, 30m, 45m, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Also, [2] reported that groundwater is a vital relevance for domestic and industrial operations as well as the environment. Due to its growing importance, [3] and [4] have also highlighted the essential functions of groundwater, and reported that a good and balance quality water is essential for the subsistence of all living organism. However, [5] reported that human beings have carelessly contaminated the groundwater through dumping of refuse in non-controlled waste facilities in an attempt to dispose solid waste.…”
Section: Introductionmentioning
confidence: 99%
“…Also, [2] reported that groundwater is a vital relevance for domestic and industrial operations as well as the environment. Due to its growing importance, [3] and [4] have also highlighted the essential functions of groundwater, and reported that a good and balance quality water is essential for the subsistence of all living organism. However, [5] reported that human beings have carelessly contaminated the groundwater through dumping of refuse in non-controlled waste facilities in an attempt to dispose solid waste.…”
Section: Introductionmentioning
confidence: 99%